British literature in transition, 1940-1960 : postwar - Plain, Gill (Cambridge : Cambridge University Press, 2019)
'Postwar' is both a period and a state of mind, a sensibility comprised of hope, fear and fatigue in which British society and its writers paradoxically yearned both for political transformation and a nostalgic re-instatement of past securities. From the Labour landslide victory of 1945 to the emergence of the Cold War and the humiliation of Suez in 1956, this was a period of radical political transformation in Britain and beyond, but these changes resisted literary assimilation. Arguing that writing and history do not map straightforwardly one onto the other, and that the postwar cannot easily be fitted into the explanatory paradigms of modernism or postmodernism, this book offers a more nuanced recognition of what was written and read in the period. From wartime radio writing to 1950s travellers, cold war poetry to radical theatre, magazine cultures to popular fiction, this volume examines important debates that animated postwar Britain.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: English literature -- 20th century -- History and criticism